Boris Pahor's prose in Italian and French - Mezeg, Adriana (Annales. Series historia et sociologia, 2022)
This article discusses Boris Pahor’s novel Vila ob jezeru in Italian and indirect French translation. After an introduction to Pahor’s language and style and an overview of his works translated into Italian and French, we highlight the main differences between the two Slovenian editions of Vila ob jezeru (1955 and 1993) and the three Italian versions (2002, 2004 and 2012). The analysis focuses on the translation of proper nouns, footnotes and stylistically marked vocabulary, and reveals some significant deviations from the source text in both target languages, although not always in the same places, showing that the Italian manuscript submitted to the French translator must have been significantly modified later by the Italian publisher.
Keywords: colloquial expressions; dialect; dialekt; footnotes; francoščina; French; Italian; italijanščina; lastna imena; opombe; Pahor, Boris; pogovorni izrazi; prevajanje; proper nouns; translation